Fast microstructure and phase analyses of nanopowders using combined analysis of transmission electron microscopy scattering patterns. Issue 5 (16th July 2014) - Boullay, P.; Lutterotti, L.; Chateigner, D.; Sicard, L.
<x xml:space="preserve">Abstract</x> The full quantitative characterization of nanopowders using transmission electron microscopy scattering patterns is shown. This study demonstrates the feasibility of the application of so‐called combined analysis, a global approach for phase identification, structure refinement, characterization of anisotropic crystallite sizes and shapes, texture analysis and texture variations with the probed scale, using electron diffraction patterns of TiO2 and Mn3O4 nanocrystal aggregates and platinum films. Electron diffraction pattern misalignments, positioning, and slight changes from pattern to pattern are directly integrated and refined within this approach. The use of a newly developed full‐pattern search–match methodology for phase identification of nanopowders and the incorporation of the two‐wave dynamical correction for diffraction patterns are also reported and proved to be efficient.